Assessing Façade Modification of Heritage Shophouses in Klang Royal Town, Selangor - Nur Nazihah Kamarul Zafik; Rohaslinda Ramele Ramli; Ahmad Nazrin Aris Anuar; Abdullah Anas Abu Bakar; Nadia Widyawati Madzhi (Research in Management of Technology and Business, 2024)
Klang was known worldwide since the 15th century for its tin industry and status as the royal capital before Kuala Lumpur. It has become overgrown since the arrival of the British Government after 1874. Nevertheless, many heritage buildings, mainly the shophouses, have been transformed and modernized to follow current trends for commercial purposes. This study aims to reveal the history of Klang Royal Town; highlight regulations and acts regarding façade modification on heritage shophouses; and assess the current state of façade modifications done on selected heritage shophouses in Klang Royal Town. Six heritage shophouses have been chosen as samplings to be analysed on the elements of façade modification, having undergone minor, moderate to major modifications. These façades are compared with photographs taken in 1987 and the modifications evaluated in the context of relevant guidelines and acts. The results show that most of the heritage shophouses in Klang Royal Town face the same issue of uncontrolled façade modification and serving current design trends to compete commercially with other shophouses. This study emphasizes the impact of these façade transformations and the heritage buildings’ historical significance from the upkeeping and safeguarding of heritage buildings’ value.